Dampak Etnosentrime dan Budaya Populer Terhadap Sikap Konsumen Serta Implikasinya Terhadap Minat Beli Konsumen - Sumiati Sumiati (Universitas Tarumanagara, 2020)
The purpose of this study is to analyze the impact of ethnocentrism, and korean wave toward attitude and implications to purchase intention for product cosmetic korea in Indonesia. This paper used quantitative method using Structural Equation Modeling (SEM) using AMOS 20 software. In total, 195 respondents completed a questionnaire were used Likert Scale with 1-5 score. The results of this study showed consumer ethnocentrism have negative significant impact on Attitude and purchase intention, Korean wave have postive significant impact on Attitude and purchase intention and Attitude have postive significant impact on Purchase Intention.